As implicações psicossociais do trabalho precoce em adultos - Santos, Denise Pereira dos (2011)
The objective of this dissertation is to analyse psychosocial implications of the precocious work for adults. For this, it was adopted as theoretical referential Vigotski s Historic-cultural Psychology to comprehend the consciousness and experience; it was opted for classical authors like Marx (1987), Engels (1985) e Thompson (1987) and contemporaneous like Antunes (2000) e Valla (2005) to define the category objective conditions of life. To define precocious work, it was chosen the conceptions of Costa (1990) and Alberto (2002). In terms of method, it was used as instrument the open interview leaded by a guide inspired in the technical of life s history, that contemplated four blocks, objective conditions of life in the childhood, precocious work, conditions of adult life and implications of the precocious work to the adult life. It was interviewed seven participants, from 31 to 55 years old, and it was used to delimitate the sample, the saturation criterion of Minayo (2008). The technical of analysis adopted was the analysis of discursive practices of Spink (2004), in which it was sought to identify the repertoires of meaning of the participants about a thematic, by using maps and trees of association of ideas. Data showed that participants, during childhood, had migration history, financial needs, creation by only one of the parents and domestic violence in some cases. Participants identified that entry into work happened around seven years old, mostly, into domestic work, agriculture, open air markets and into the streets, to work to family or to others. The work activities were marked by many hours of work and by low payment or even absence of payment. The meaning of the discourse of the participants reveals implications, both positive and negative. Among positive ones, they reproduce the society s discourse about precocious work as training and responsibility. Among positive ones, they reproduce the society s discourse about precocious work as training and gives responsibility. At the same time, precocious work appears as being negative by: disrupting schooling; bringing, to some participants, implications for health and for obtaining employment in the current life; promoting the loss of childhood; and bringing implications to relationship with sons. Current life is marked by informal employment or unemployment, and the benefit of the Programa Bolsa Família (Governmental Program to help low-income families) has an important function in maintaining family. It is concluded that, to these participants, the meanings that precocious work assumes are contradictories; it is seen as bringing positive and negative implications at the same time, besides showing that there is a fragmented consciousness about their histories and about relation between their past and present. It is comprehended that precocious work brings marks to subjectivity of these subjects at the moment it denies to them the access to schooling and to knowledge available in their culture, takes away from them or reduces the experience of essential activities to development, like playing, and brings implications to the construction of identity, due to precocious responsibility assumed.